2011
DOI: 10.1136/bmjopen-2011-000257
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of postpartum haemorrhage in women receiving therapeutic doses of low-molecular-weight heparin: results of a retrospective cohort study

Abstract: BackgroundLow-molecular-weight heparin (LMWH) is the drug of choice to prevent venous thrombosis in pregnancy, but the optimal dose for prevention while avoiding bleeding is unclear. This study investigated whether therapeutic doses of LMWH increase the incidence of postpartum haemorrhage (PPH) in a retrospective controlled cohort.MethodsAll pregnant women who received therapeutic doses of LMWH between 1995 and 2008 were identified in the Academic Medical Center, Amsterdam, The Netherlands. The controls were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 24 publications
0
55
0
Order By: Relevance
“…Roshani et al (2011) observed that therapeutic dose of LMWH was not associated with a clinically meaningful increase in PPH or severe PPH in 95 women delivered in their hospital. Knol et al (2012) concluded from their study of 88 women that high dose LMWH was associated with an increased risk of >500 ml blood loss after vaginal delivery (30% as compared to 18% in non-users) and that the risk of severe PPH after caesarean section was 12% in LMWH users and 4% in non-users.…”
mentioning
confidence: 86%
“…Roshani et al (2011) observed that therapeutic dose of LMWH was not associated with a clinically meaningful increase in PPH or severe PPH in 95 women delivered in their hospital. Knol et al (2012) concluded from their study of 88 women that high dose LMWH was associated with an increased risk of >500 ml blood loss after vaginal delivery (30% as compared to 18% in non-users) and that the risk of severe PPH after caesarean section was 12% in LMWH users and 4% in non-users.…”
mentioning
confidence: 86%
“…It has been postulated that an intermediate dose of LMWH could have superior efficacy compared to a prophylactic dose of LMWH, but potentially at the cost of a higher bleeding risk. Reassuringly, in a retrospective study in pregnant women receiving therapeutic doses of LMWH, there was no increased risk of clinically relevant or severe postpartum bleeding compared with women who had delivered in the same hospital without LMWH use [20]. In another study, women receiving therapeutic LMWH during pregnancy were found to have an increased risk of blood loss N500 mL and b1000 mL after vaginal delivery [21].…”
Section: Introductionmentioning
confidence: 97%
“…58 However, a recent small study confirms earlier observations of neonatal anti-factor Xa levels at ≈10% of maternal levels. 45,59 This raises the possibility that fondaparinux may cross the human placenta in small doses. Prior studies on the safe and effective use of fondaparinux have used the same weight-based prophylactic and therapeutic doses used in the nonpregnant population.…”
Section: Factor Xa Inhibitorsmentioning
confidence: 99%
“…44 The lack of increase in postpartum hemorrhage among pregnant women using enoxaparin is supported in other studies. 45 The theoretical potential for increased bleeding may be mitigated by strategic timing of doses relative to labor and delivery. The blood loss among women using LMWH may be reduced by stopping therapy 24 hours before the onset of labor or converting to UFH as described above.…”
Section: Low-molecular-weight Heparinmentioning
confidence: 99%